Perioperative Low Dose Dexmedetomidine and Its Effect on the Visibility of the Surgical Field for Middle Ear Microsurgery: A Randomised Controlled Trial - Wu, Jinhong; Han, Yuan; Lu, Yu; Zhuang, Yan; Li, Wenxian; Jia, Ji’e (Frontiers in Pharmacology, 2022)
Background and Purpose There are many benefits of administering dexmedetomidine perioperatively. The pharmacokinetics (PK) and pharmacodynamics (PD) of intravenous, intranasal and oral dexmedetomidine that was administered before anesthesia were compared in this study, and the effects of dexmedetomidine on the surgical field visibility in tympanoplasty was evaluated. Methods A single-blind, randomized controlled trial was conducted in a university-affiliated hospital where 45 patients who underwent tympanoplasty under general anesthesia were randomly allocated into three groups. Dexmedetomidine was administered by intravenous infusion at 0.8 μg.kg-1 for 10 min, intranasal instillation at a drop rate of 1 μg.kg-1 and oral intake at 4 μg.kg-1 ten minutes before the induction of anesthesia. The PK and PD of dexmedetomidine after a single low dose administration and its effect on the surgical field in tympanoplasty were analysed. Results: A plasma concentration of dexmedetomidine of 220 pg/mL was achieved immediately after intravenous infusion and at 13.2 min and 70.3 min for intranasal and oral administration, respectively. Dexmedetomidine decreased the heart rate (HR) and mean arterial pressure (MAP) in all three groups, although these values remained higher in the oral dexmedetomidine group at all eight time points. Intravenous dexmedetomidine provided the best visualization of the surgical field for opening of the tympanic sinus, 30 min after the start of the infusion (P<0.05). Intranasal dexmedetomidine provided a significantly better visual field than oral dexmedetomidine for the repair of a tympanic membrane perforation using the fascia temporal muscle (P<0.05). Conclusion: A single low dose of dexmedetomidine administered intravenously or intranasally could decrease HR and MAP, improve surgical field visibility and be appropriate for deliberate hypotension for surgical procedures of 1-2 h in length.